2007
DOI: 10.1088/0004-6256/135/1/348
|View full text |Cite
|
Sign up to set email alerts
|

The Sloan Digital Sky Survey-Ii Supernova Survey: Search Algorithm and Follow-Up Observations

Abstract: The Sloan Digital Sky Survey-II Supernova Survey has identified a large number of new transient sources in a 300 deg 2 region along the celestial equator during its first two seasons of a three-season campaign. Multiband (ugriz) light curves were measured for most of the sources, which include solar system objects, galactic variable stars, active galactic nuclei, supernovae (SNe), and other astronomical transients. The imaging survey is augmented by an extensive spectroscopic follow-up program to identify SNe,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
183
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 206 publications
(187 citation statements)
references
References 52 publications
2
183
0
2
Order By: Relevance
“…At very high redshifts, HST surveys (Riess et al, 2004Suzuki et al, 2012) have yielded ∼ 25 Type Ia SNe at z > 1.0, which confirm the expectation that the universe was decelerating at high redshift and limit possible systematic effects from evolution of the supernova population or intergalactic dust extinction. At intermediate redshifts (0.1 < z < 0.4), the SDSS-II supernova survey Sako et al, 2008) has discovered and monitored 500 spectroscopically confirmed Type Ia SNe; only the first-year data set (103 SNe) has so far been subjected to a full cosmological analysis (Kessler et al, 2009 present cosmological results from a sample of 752 photometrically classified SDSS-II SNe with spectroscopic host galaxy redshifts, and a joint analysis of the SNLS and SDSS-II samples is in process (J. Frieman, private communication). Finally, the last five years have also seen major efforts to expand the sample of local calibrators and improve their measurements, including rest-frame IR and rest-frame UV photometry (Wood-Vasey et al, 2008;Stritzinger et al, 2011;Contreras et al, 2010;Hicken et al, 2009a).…”
Section: The Current State Of Playmentioning
confidence: 99%
“…At very high redshifts, HST surveys (Riess et al, 2004Suzuki et al, 2012) have yielded ∼ 25 Type Ia SNe at z > 1.0, which confirm the expectation that the universe was decelerating at high redshift and limit possible systematic effects from evolution of the supernova population or intergalactic dust extinction. At intermediate redshifts (0.1 < z < 0.4), the SDSS-II supernova survey Sako et al, 2008) has discovered and monitored 500 spectroscopically confirmed Type Ia SNe; only the first-year data set (103 SNe) has so far been subjected to a full cosmological analysis (Kessler et al, 2009 present cosmological results from a sample of 752 photometrically classified SDSS-II SNe with spectroscopic host galaxy redshifts, and a joint analysis of the SNLS and SDSS-II samples is in process (J. Frieman, private communication). Finally, the last five years have also seen major efforts to expand the sample of local calibrators and improve their measurements, including rest-frame IR and rest-frame UV photometry (Wood-Vasey et al, 2008;Stritzinger et al, 2011;Contreras et al, 2010;Hicken et al, 2009a).…”
Section: The Current State Of Playmentioning
confidence: 99%
“…Much of the material in this section is also relevant to the SN rate studies described by Dilday et al (2010), and is discussed more fully therein. The survey is described in more detail by Frieman et al (2008), and the SN detection algorithms are given by Sako et al (2008). Additional details of the survey observations and the use of in situ artificial SNe for determining SN detection efficiencies are discussed by Dilday et al (2008).…”
Section: Sdss-ii Supernova Survey Observationsmentioning
confidence: 99%
“…As a key component of prioritizing SN candidates for follow-up spectroscopic observations, the light curves of SN candidates were fit to models of Type Ia, Type Ib/c, and Type II SNe (see Filippenko 1997 for a review of SN types). This procedure is referred to as "photometric typing," and is described in detail by Sako et al (2008).…”
Section: Sdss-ii Supernova Survey Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2005, the SNfactory pioneered the use of machine learning algorithms to replace "cuts" for supernova object detection [9], and since then, such techniques have been utilized by other supernova searches, including SDSS and SNLS [16,17]. The SDSS "autoscanner" uses a combination of heuristics and a naive Bayes classifier to filter out non-SN objects, but they do not provide a comparison of the efficacy of any other types of machine learning algorithms for supernova search.…”
Section: Related Workmentioning
confidence: 99%